A new multimedia–oriented architecture and protocol for wireless ad hoc networks. (10th June 2014) - Diaz, Juan R.; Lloret, Jaime; Jiménez, Jose M.; Hammoumi, Mohammed
The number of smart phones, tablets, PDAs and other type of mobile devices used regularly by the population is growing fast. They are able to offer high processing capacities while having several wireless interfaces. Wireless ad hoc networks are currently widely used to share resources between users. In this paper, we propose a new multimedia–oriented application layer protocol. It takes into account the multimedia services offered by the nodes in the wireless ad hoc network to select the best multimedia service provider node and to provide the best QoE and quality of service (QoS) to the nodes participating in the ad hoc network. We will explain the designed protocol and decision algorithms to provide the best multimedia service to the end users. Then, we will show a study case and we will validate our proposed system through the measurements taken from a real test bench. There is no protocol designed such as the one presented in this paper.